Tháng Tư 16, 2024

Rút gọn : a) \(A = \frac{1}{{\sqrt 5 – 1}} + \frac{1}{{\sqrt 5 + 1}}\) b) \(B = \frac{1}{{\sqrt 1 + \sqrt 2 }} + \frac{1}{{\sqrt 2 + \sqrt 3 }} + … + \frac{1}{{\sqrt {99} + \sqrt {100} }}\) A a)\(A=\frac{\sqrt{5}}{2}\) b) B=10 B a)\(A=\frac{\sqrt{7}}{2}\) b) B=9 C a)\(A=\frac{\sqrt{5}}{2}\) b) B=9 D a)\(A=\frac{\sqrt{5}}{3}\) b) B=9

Rút gọn :

a) \(A = \frac{1}{{\sqrt 5 – 1}} + \frac{1}{{\sqrt 5 + 1}}\) b) \(B = \frac{1}{{\sqrt 1 + \sqrt 2 }} + \frac{1}{{\sqrt 2 + \sqrt 3 }} + … + \frac{1}{{\sqrt {99} + \sqrt {100} }}\)

A a)\(A=\frac{\sqrt{5}}{2}\)

b) B=10

B a)\(A=\frac{\sqrt{7}}{2}\)

b) B=9

C a)\(A=\frac{\sqrt{5}}{2}\)

b) B=9

D a)\(A=\frac{\sqrt{5}}{3}\)

b) B=9

Hướng dẫn Chọn đáp án là: C

Phương pháp giải:

a) Sử dụng biểu thức liên hợp.

b) Sử dụng biểu thức liên hợp.

Lời giải chi tiết:

\(\begin{array}{l}a)\,\,A = \frac{1}{{\sqrt 5 – 1}} + \frac{1}{{\sqrt 5 + 1}} = \frac{{\sqrt 5 + 1}}{{(\sqrt 5 – 1)(\sqrt 5 + 1)}} + \frac{{\sqrt 5 – 1}}{{\left( {\sqrt 5 + 1} \right)\left( {\sqrt 5 – 1} \right)}}\\\,\,\,\,\,A = \frac{{\sqrt 5 + 1}}{4} + \frac{{\sqrt 5 – 1}}{4} = \frac{{\sqrt 5 }}{2}\\b)\,\,B = \frac{1}{{\sqrt 1 + \sqrt 2 }} + \frac{1}{{\sqrt 2 + \sqrt 3 }} + … + \frac{1}{{\sqrt {99} + \sqrt {100} }}\\\,\,\,\,\,B = \frac{1}{{\sqrt 2 + \sqrt 1 }} + \frac{1}{{\sqrt 3 + \sqrt 2 }} + … + \frac{1}{{\sqrt {100} + \sqrt {99} }}\\\,\,\,\,\,B = \frac{{\sqrt 2 – \sqrt 1 }}{{2 – 1}} + \frac{{\sqrt 3 – \sqrt 2 }}{{3 – 2}} + \frac{{\sqrt 4 – \sqrt 3 }}{{4 – 3}}… + \frac{{\sqrt {100} – \sqrt {99} }}{{100 – 99}}\\\,\,\,\,\,B = – \sqrt 1 + \sqrt {100} = – 1 + 10 = 9\end{array}\)